Interleukin 6 and 10 Serum Levels and Genetic Polymorphisms in Children with Down Syndrome - Mattos, Marlon Fraga; Biselli-Chicote, Patrícia Matos; Biselli, Joice Matos; da Silva Assembleia, Thiago Luís; Goloni-Bertollo, Eny Maria; Pavarino, Érika Cristina (Mediators of Inflammation, 2018)
Immunological impairment is a condition that is often observed in individuals with Down syndrome (DS). The immune response is modulated by pro- and anti-inflammatory cytokines whose expressions could be influenced by genetic polymorphisms. The present study was aimed at evaluating the frequencies of -174G>C, -572G>C, and -597G>A polymorphisms in the interleukin 6 (IL-6) gene and -592C>A, -1082A>G, and -819C>T polymorphisms in the IL-10 gene and the IL-6 and IL-10 serum levels in healthy individuals with and without DS. The authors also aimed to investigate the impact of the genotypes on the interleukin concentrations. The genetic polymorphisms were investigated in 200 DS individuals and 200 controls without DS. The serum measurement of IL-6 and IL-10 was performed in a subgroup (54 cases and 54 controls) by enzyme-linked immunosorbent assay (ELISA). The frequencies of the polymorphisms and haplotypes evaluated were not different between individuals with and without DS. IL-10 concentration was higher in DS children but was not influenced by IL-10 gene polymorphisms. IL-6 genotypes had no influence on IL-6 serum levels. The IL-10 serum levels are increased in DS individuals, but IL-10 polymorphisms are not the main factors that influence the IL-10 expression in DS.